2019
DOI: 10.1002/open.201800259
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into a Stibene Cleavage Oxygenase NOV1 from Quantum Mechanical/Molecular Mechanical Calculations

Abstract: NOV1, a stilbene cleavage oxygenase, catalyzes the cleavage of the central double bond of stilbenes to two phenolic aldehydes, using a 4‐His Fe(II) center and dioxygen. Herein, we use in‐protein quantum mechanical/molecular mechanical (QM/MM) calculations to elucidate the reaction mechanism of the central double bond cleavage of phytoalexin resveratrol by NOV1. Our results showed that the oxygen molecule prefers to bind to the iron center in a side‐on fashion, as suggested from the experiment. The quintet Fe−O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 62 publications
(131 reference statements)
1
6
0
Order By: Relevance
“…However, the end-on structure in the quintet state, which is the reactive state for the BTG13-catalyzed reaction, is 3.5 kcal/mol lower than that of the side-on structure. The former mode is thus proven to be more energetically favorable, which is consistent with the findings in other dioxygenases. , Therefore, in this work, the end-on mode was considered as the starting point of the catalytic reaction.…”
Section: Resultssupporting
confidence: 83%
“…However, the end-on structure in the quintet state, which is the reactive state for the BTG13-catalyzed reaction, is 3.5 kcal/mol lower than that of the side-on structure. The former mode is thus proven to be more energetically favorable, which is consistent with the findings in other dioxygenases. , Therefore, in this work, the end-on mode was considered as the starting point of the catalytic reaction.…”
Section: Resultssupporting
confidence: 83%
“…A separate QM/MM study proposed that the oxidizing species was a side-on Fe(II) superoxo radical. 194 However, both computational works were based on a problematic crystal structure; thus, the precise mechanism is still unknown. 195 As we further our understanding of the reaction mechanism of CCOs, we propose that a +2 charge will remain constant throughout the catalytic cycle.…”
Section: Nonheme Iron Oxygenases With a 4-hismentioning
confidence: 99%
“…There is still debate surrounding the mechanism of CCOs. A separate QM/MM study proposed that the oxidizing species was a side-on Fe­(II) superoxo radical . However, both computational works were based on a problematic crystal structure; thus, the precise mechanism is still unknown .…”
Section: Nonheme Iron Oxygenases With a 4-his Ligand Scaffoldmentioning
confidence: 99%
“…The protonation states of Lys134 and 4'-hydroxyl minimally affected the transition state energies suggesting that the interaction between these two groups is strictly for proper substrate positioning rather than to enable proton shuttling. The study by Lu, et al found the initial reactive state to be a side-on Fe II -O 2 − complex with partial electron transfer from resveratrol to the iron-oxy complex [78]. For the quintet spin state, the unpaired electrons on O 2 and resveratrol have anti-parallel spins suitable for peroxo bridge formation between O 2 and the α-carbon of resveratrol.…”
Section: Computational Studiesmentioning
confidence: 99%